Checklist of wild mammals of Shivapuri Nagarjun National Park, Nepal - Poudyal, Laxman Prasad; Koju, Narayan Prasad; Bista, Manjit; Thapa, Sanjan; Dahal, Dibya Raj; Khadka, Saroj; Pandey, Bishnu Prasad (Nepalese Journal of Zoology, 2023)
An updated checklist of mammalian richness is an important tool for biodiversity conservation and management of protected areas. In this study, we present the updated checklist of wild mammals of Shivapuri Nagarjun National Park (SNNP) in the central mid-hill of Nepal based on direct observation, field reports, key informant interviews, and a literature review. A total of 65 species of mammals belonging to eight orders and 22 families were known to occur in the park. Order Rodentia (n=21, 32.30%) and family Muridae (n=14, 21.53%) have the highest record of the number of species. Out of 65 mammal species, 53 species (81.53%) were confirmed for their occurrence either by direct observation and camera trap. Only 12 species were listed based on literature review and personal communication. In SNNP, 1.53% of mammalian species are listed as critically endangered species 9.23% are under vulnerable; 6.15% of the species are listed as endangered in the National Red List. The confirmation for small mammals needs further study for robust taxonomy and we suggest molecular study of species having contradictory taxonomy.